Structural and Functional Approach to the Assessment of the Educational Programs Quality - A. A. Pochestnev (Высшее образование в России)
The article is devoted to the use of social diagnostics based on structural and functional methodology to assess the quality of bachelor’s educational programs. The main components of this technology are situational analysis of programs, which more accurately determines the purpose of diagnostics and criteria for assessing, and a structural-functional model that allows to determine dysfunctional zones in the structure of education and their causes.The approbation of this diagnosis was carried out on the educational program of bachelors in Social Management at the Moscow Aviation Institute. Focus groups and questionnaires of graduate students were the main methods of data collection.The diagnostic results allowed us to determine that the vector of students’ needs in the field of education coincides with the competence model of the program. The decline in the quality of the program occurs due to the low level of development of practical skills and analytical competencies. The subjective perception of students about the structural factors of the decline in the quality of education was also determined. These are the factors of organization and the type of interaction between professors and students.Structural and functional diagnostics showed the absence of uniform institutional requirements for the educational program and the problems of its organization.The data obtained can be used in the management of the educational program. From a scientific point of view, the results are a contribution to the development of sociological diagnostic tools based on a situational approach and understanding of modern values of youth in the field of education.